1999
DOI: 10.1007/pl00011811
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Measurement of Methanogens in the Sediments of Tokyo Bay Using Archaeol Lipids

Abstract: An archaeal ether-linked lipid, archaeol, was determined to be a biomass indicator for methanogens both in the laboratory enriched culture and in marine sediments. The archaeol measurement method described by Ohtsubo et al. in 1993 was modified and applied to marine sediments. We compared the amount of archaeol with the cell number of methanogens or methane concentration in laboratory enriched culture of methanogens from marine sediment. Good correlations were obtained as follows: (Methane, mmol) = 11.2 x (Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For example, phytane-related isoprenoids released after the cleavage of polar lipids have been detected in abundance in the hypersaline microbial mats of Shark Bay, Western Australia, and Laguna Guerrero Negro, Mexico (53,54). Originating from archaeol, such compounds are indicative of methanogens found in a range of environments including microbial mats (55)(56)(57). In algae, n-alkyl lipids (e.g., C 17-19 n-alkanes) are depleted in 13 C compared to the cooccurring isoprenoids by ∼1.5‰, whereas in bacteria, the opposite pattern is observed (ref.…”
Section: Compound-specific Isotope Analysis Of the Cie Supports Its Environmentalmentioning
confidence: 99%
“…For example, phytane-related isoprenoids released after the cleavage of polar lipids have been detected in abundance in the hypersaline microbial mats of Shark Bay, Western Australia, and Laguna Guerrero Negro, Mexico (53,54). Originating from archaeol, such compounds are indicative of methanogens found in a range of environments including microbial mats (55)(56)(57). In algae, n-alkyl lipids (e.g., C 17-19 n-alkanes) are depleted in 13 C compared to the cooccurring isoprenoids by ∼1.5‰, whereas in bacteria, the opposite pattern is observed (ref.…”
Section: Compound-specific Isotope Analysis Of the Cie Supports Its Environmentalmentioning
confidence: 99%
“…These findings strongly suggest new archaea species producing these lipids in marine environments at not high temperatures and ubiquitous distribution of archaea on Earth in accordance with 16S rRNA ecology. 60,61) HPLC analysis of archaeal core lipids was applied to quantitation of cell masses of methanogenic archaea in given environmental samples, such as anaerobic sewage sludge, 62) paddy field soil, 63) and marine sediments of Tokyo Bay, 64) and information was obtained. This method is inevitably accompanied by the weakness that it cannot discriminate whether detected core lipids were derived from living cells, or were accumulated lipid released from dead cells.…”
Section: Taxonomic and Ecological (Environmental) Aspectsmentioning
confidence: 99%
“…Archaeal diether core lipids have been proposed as a methanogen biomarker or to estimate quantitatively methanogen biomass in natural systems. Respective studies have predominantly been restricted to highly anaerobic environments exhibiting significant CH 4 emissions such as rice paddies [16, 17], digester sludge [18, 19], marine sediment [20], faecal material [21], permafrost [22, 23], and peatlands [2426]. Wachinger et al [27] observed that absolute Archaea cell numbers in mineral soils, calculated using the approximate ether lipid concentration 2.5  μ mol g −1 dry weight of methanogen cells [28], also reflected CH 4 productivity.…”
Section: Introductionmentioning
confidence: 99%